Demonstrating the importance of interprofessional health education through an interactive case competition at Queen’s Faculty of Health Sciences - Aggarwal, Ishita; Jane, Alanna; Patel , Rupa (Canadian Medical Education Journal, 2023)
Implication Statement On March 4, 2021, OSLER Kingston and KHealth, student-run organizations at Queen’s Faculty of Health Sciences, hosted a two-hour-long virtual interprofessional case competition called “OSLER x KHealth IPR Case Competition: Homelessness,” focusing on housing insecurity and homelessness. This event demonstrated that integrating interprofessional education (IPE) competencies into educational experiences of health professional students is feasible to organize and implement while also being valuable. Students who participated found IPE to be helpful for their learning. Consequently, we encourage medical school curriculum leaders and student-led groups to prioritize IPE in their preclerkship curricular and extracurricular offerings.